48V EGR Pump System Development and Fuel Benefit Evaluation - Bagal, Nilesh L.; Bhardwaj, Divyanshu (Frontiers in Mechanical Engineering, 2022)
Heavy duty (HD) diesel engines use exhaust gas recirculation (EGR) to help reduce engine out NOx and meet emission regulations. One of primary ways of doing this is to recirculate exhaust gas from the exhaust manifold, cool it, and introduce to the intake system. Exhaust manifold pressure is maintained higher than intake pressure to flow exhaust gases to the intake. This is done by closing vane positions in the case of variable geometry turbines (VGT) or wastegate (WG) operation for a fixed geometry turbine (FGT). The turbine operates at lower efficiency in order to maintain higher back pressure, thus affecting intake boosting capability. A negative engine delta pressure helps drive EGR flow and reduce engine out NOx, but at the expense of increased pumping power and thus lower engine efficiency or more fuel consumption. The Eaton EGR pump is based on Eaton TVS™ rotor technology. It is driven by a 48V electric motor and thus decouples the engine EGR flow requirement from the turbine. The turbine can then be optimized to provide the required boost pressure for charge air with improved efficiency and lower engine delta pressure. This paper presents a model-based development and value proposition analysis of EGR pump at Eaton. CFD analysis of the pump is discussed, including pressure pulsation and noise reduction. Also, GT-POWER analysis is used to evaluate fuel consumption improvements of the EGR pump along with optimized air system and engine calibration. Analysis led product development is important to developing robust hardware with minimum time and engineering resources. EGR pump prototypes are currently being tested for durability and on engine for performance validation.